Context-dependent functionality of 2′-fucosyllactose with Bifidobacterium breve M-16 V and short-chain galacto−/long-chain fructo-oligosaccharides in infant gut fermentation - Wenbo Guo; Binghui Zhou; Youlan An; Huiying Qiu; Lintao Zhang; Xianfeng Zhao; Xinyu Li; Bowen Shi; Ao Liu; Xiaoze Pang; Zhe Wang; Xinjie Zhu; et al. (Food Research International, 2026)

The Anti-Fibrotic Effects of Irisolidone via Peroxisome Proliferator-Activated Receptor Gamma - Zi-an Pan; Li-ting Tong; Zhe-min Wang (Tissue and Cell, 2026)

Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

Precise nanodelivery of screened compounds alleviates sepsis-associated encephalopathy by targeting microglial ANXA2 - Daoyi Lin; Yuan Huang; Shuyan Wu; Zefu Li; Hanhao Dai; Fei Gao; Danfeng Wang; Maokai Xu; Ziqi An; Xinmu Li; Peng Ye; Yingjie Chen; et al. (Science Bulletin, 2026)

Screening of proteins interacting with vhvp-2 protein from Vibrio parahaemolyticus causing translucent post-larvae disease in Pacific white shrimp Litopenaeus vannamei - Na An; Li Jiang; Yilin Wang; Zhe Du; Yun Wei; Qifan Zeng; Mengqiang Wang (Journal of Invertebrate Pathology, 2026)

IL-33 Regulates the Phenotypic Transformation of Reactive Astrocytes via PENK-ERK/MAPK Pathway in Parkinson’s Disease - Yi Qu; Zhijuan Mao; Danlei Wang; Ke An; Haoheng Yu; Qixiong Qin; Jingyi Li; Yongjie Xiong; Zhe Min; Zheng Xue (Neuroscience Bulletin, 2026)
Interleukin-33 (IL-33) regulates immune responses in central nervous system diseases. This study investigates the effect of IL-33 on astrocyte phenotypic transformation in Parkinson’s disease (PD). The associations of IL-33, soluble growth-stimulating expression gene 2 (sST2), with PD severity and clinical symptoms were examined. IL-33 supplementation and knockdown were applied in vivo and in vitro to assess IL-33’s impact on neuron loss, astrocyte polarization, and inflammation. Transcriptome sequencing was conducted to identify hub genes and pathways regulated by IL-33 in astrocytes, with validated in primary astrocytes. Plasma sST2 levels were elevated in PD patients and correlated with PD severity, while IL-33 decreased with disease progression. In PD models, IL-33 supplementation improved PD-like symptoms and A2 astrocyte polarization. Conversely, IL-33 knockdown worsened PD-like symptoms and neurotoxic polarization. RNA-seq identified the PENK-ERK/MAPK pathway as the key regulator of IL-33-mediated astrocyte transformation. In conclusion, IL-33 plays a crucial role in regulating astrocytes in PD.

Structural controlling conditions for dry hot rock reservoirs in the middle section of the northern margin in the North China Block - Yan-Xu Liu; Wen-Yong Li; Shan-Gao; An-Qi Cao; Zhe-Xin Jiang; Wei-di Meng (Applied Geophysics, 2026)

Sustainable catalyst design: Magnesia slag-doped MS-LDHs fabricated via pulsed laser trapping for efficient and green Cr(VI) adsorption - Ren-yun Zhang; Yan Liu; Zhi-yu Fan; Hong-xuan Xing; Ji-dong Li; Qiu-yu Huang; Zhe Jin; Ting-an Zhang (Journal of Cleaner Production, 2026)

Responses of soil bacterial community structure across mining age and soil depth scales in coal mining subsidence zones - Zhe Wang; Lei Zhang; Yijie An; Feng Xu; Shuo Li; Hua Cai (Plant and Soil, 2026)

Construction and application of a high-resolution pollen numerical model system based on phenology and XGBoost - Jiangtao Li; Xingqin An; Zhe Liu; Fan Zhao; Huaerqi Huang; Qing Hou; Yu Wang (Environmental Pollution, 2026)

Sensitivity analysis of PM2.5 and O3 co-pollution in Beijing based on GRAPES-CUACE adjoint model - Zhe Liu; Xingqin An; Chao Wang; Jiangtao Li; Meng Cui (Journal of Environmental Sciences, 2025)

Screening of proteins interacting with infectious hypodermal and hematopoietic necrosis virus in Pacific white shrimp Litopenaeus vannamei - Na An; Li Jiang; Zhe Du; Yilin Wang; Mengqiang Wang (Fish & Shellfish Immunology, 2025)

Corrigendum to “Study on cable flame spread in utility tunnel under different reverse ventilation and cable layer spacing” [Tunn. Undergr. Space Technol. 162 (2025) 106671] - Tongcheng Zhang; Xiaoshan Wang; Zhe Wang; Junyi Li; Weibin An; Feixiang Xu; Weiguang An (Tunnelling and Underground Space Technology, 2025)

Transmembrane uptake of polystyrene nanoplastics mediated by aquaporin in tartary buckwheat: Physiological consequence and genomic mechanism - Yu-Kang Hou; Shuo Gao; Qiang Lai; Wen-Rui Lu; You-Bao Cai; Ya-Wen Yuan; Si-Yuan Yao; Hong-Yan Tao; Li-Zhe An; You-Cai Xiong; Yuan Song (Journal of Hazardous Materials, 2025)

Study on cable flame spread in utility tunnel under different reverse ventilation and cable layer spacing - Tongcheng Zhang; Xiaoshan Wang; Zhe Wang; Junyi Li; Weibin An; Feixiang Xu; Weiguang An (Tunnelling and Underground Space Technology, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Review of glass-ceramics: Solidification of toxic elements and durability - Qiong Li; Bo Liu; Jiling Liu; Qian Zhang; Changcong An; Zhe Sun; Bakhtiyor Pulatov; Siyu Wei; Jiaxing Fan (Waste Management, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

Short-Chain Fatty Acid Aggregates Alpha-Synuclein Accumulation and Neuroinflammation via GPR43-NLRP3 Signaling Pathway in a Model Parkinson’s Disease - Yi Qu; Ke An; Danlei Wang; Haoheng Yu; Jingyi Li; Zhe Min; Yongjie Xiong; Zheng Xue; Zhijuan Mao (Molecular Neurobiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Synergy of dual dopants and nitrogen defects in graphitic carbon nitride for boosting sustainable photocatalytic inactivation efficiency towards antibiotic-resistant bacteria - Weixuan Li; Wanjun Wang; Chao Wang; Yiming Huang; Wenhai Liu; Weina Zhao; Zhe Xu; Guiying Li; Taicheng An (Chemical Engineering Journal, 2025)

Nanoplastics facilitate the spread of antibiotic resistance genes in chemically induced competent bacteria: The hydrogen peroxide plays as the main signal factor - Chenxi Li; Qian Zhang; Linjie Wang; Zhe Piao; Ya Zhang; Yang Chong; Xin’an Jiao; Honggui Wang (Journal of Environmental Chemical Engineering, 2025)

Assessing outdoor thermal comfort variations between residents and tourists in a hot-humid traditional village setting - Jishui Jiang; Zhe Li; Komi Bernard Bedra; Liang Xie; Yaning An; Qikang Zhong (Building and Environment, 2025)

The research of nicotinamide and β-arbutin on reducing melanin content in the skin of leopard coral grouper (Plectropomus leopardus) - Zhi Bin Sun; Shi Ying Liu; Xin An Wang; Ai Jun Ma; Zhi Hui Huang; Zhi Feng Liu; Wei Heng Sun; Peng Fei Yan; Dong Hui Gou; Hui Yu Xiao; Hao Zhe Li; Vorathep Muthuwan; et al. (Aquaculture, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Spatial-temporal characteristics and the importance of environmental factors in relation to algal blooms in coastal seas - Yanbin Tong; Kun Lei; Li Wang; Yuanyi Li; Wenlu Lan; Yuming Cheng; Zeng'an Deng; Jingsheng Zhai; Zhe Huang (Science of The Total Environment, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Bearing Performance of a Helical Pile for Offshore Photovoltaic under Horizontal Cyclic Loading - Xinfu Cong; Zhe Li; Zhonghai An; Jiangxue Liu; Yanqing Han (Journal of Marine Science and Engineering, 2024)
For an offshore photovoltaic helical pile foundation, significant horizontal cyclic loading is imposed by wind and waves. To study a fixed offshore PV helical pile’s horizontal cyclic bearing performance, a numerical model of the helical pile under horizontal cyclic loading was established using an elastic–plastic boundary interface constitutive model of the clay soil. This model was compared with a monopile of the same diameter under similar conditions. The study examined the effects of horizontal cyclic loading amplitude, period, and vertical loads on the horizontal cyclic bearing performance. The results show that under horizontal monotonic loading, the bearing capacities of a helical pile and monopile in a serviceability limit state are quite similar. However, as the amplitude of horizontal cyclic loading increases, soil stiffness deteriorates significantly, leading to greater horizontal displacement accumulation for both types of piles. The helical pile’s bearing capacity under horizontal cyclic loadings is approximately 60% of that under monotonic loading. With shorter cyclic loading periods, horizontal displacement accumulates rapidly in the initial stage and stabilizes over a shorter duration. In contrast, longer cyclic loading periods lead to slower initial displacement accumulation, but the total accumulated displacement at stabilization is greater. When vertical loads are applied, the helical pile exhibits more stable horizontal cyclic bearing performance than the monopile.

Nanopore-regulated in situ polymerization for synthesis of homogeneous heparan sulfate with low dispersity - Meng Qiao; Zhe Wang; Junjie Zhang; Yanqi Li; Liang-An Chen; Fuming Zhang; Jonathan S. Dordick; Robert J. Linhardt; Chao Cai; He Huang; Xing Zhang (Carbohydrate Polymers, 2024)

Sensitivity analysis and precursor emission sources reduction strategies of O3 for different pollution weather types based on the GRAPES-CUACE adjoint model - Chao Wang; Jiangtao Li; Xingqin An; Zhe Liu; Deyou Zhang (Atmospheric Environment, 2024)

Enhancement of beneficial microbiomes in plant–soil continuums through organic fertilization: Insights into the composition and multifunctionality - Wen-Jing Li; Xin-Yuan Zhou; Xin-Li An; Li-Juan Li; Chen-Shuo Lin; Hua Li; Hong-Zhe Li (Soil Ecology Letters, 2024)

Photo-transformation of graphitic carbon nitride synthesized from different precursors: Influence on environmental fate and photocatalytic water disinfection - Shi’en Lei; Wanjun Wang; Chao Wang; Weixuan Li; Zhe Xu; Guiying Li; Taicheng An (Journal of Water Process Engineering, 2024)

Cathepsin B degrades RbcL during freezing-induced programmed cell death in Arabidopsis - Gang Yang; Tao Chen; Ting-ting Fan; Xiang-yu Lin; Yu-qiong Cui; Wei-chao Dong; Li-zhe An; Hua Zhang (Plant Cell Reports, 2024)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Prognostic value of left ventricular systolic function on moderate aortic stenosis: the China-VHD study - Xianbao Liu; Qifeng Zhu; Qiong Liu; Haiyan Xu; Hanyi Dai; Yaoyao Zhou; Jun Chen; Stella Ng; Ye Lu; Yanyan Zhao; Zhe Li; Yongjian Wu; et al. (Science Bulletin, 2023)

Heat stress mitigation with ice cooling vests in PPE-clad medical workers: Effects of cooling area and gender differences - Zhe Li; Bing'an Pan; Bin Yang; Bin Zhou; Faming Wang (Building and Environment, 2023)

Repeated photocatalytic inactivation of E. coli by UV + Ni foam@TiO2: Performance and photocatalyst deactivation - Miao Wang; Zhe Xu; Zhenlian Qi; Yiwei Cai; Guiying Li; Wonyong Choi; Taicheng An (Chemical Engineering Journal, 2023)

Carbon nanofibers with gas selective layer containing rich and accessible ultramicropores for methane/nitrogen separation - Tian-Yi Li; Yong-Sheng Wang; Meng-Yao Zhang; Bo-Yang Liu; Zhe Zheng; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Self-assembled DNA nanoparticles enable cascade circuits for mRNA detection and imaging in living cells - Zhe Dong; Debo Gao; Yuancheng Li; Kang An; Jing Ni; Ling Meng; Han Wu (Analytica Chimica Acta, 2023)

Neuropyrones A–E, five undescribed α-pyrone derivatives with tyrosinase inhibitory activity from the endophytic fungus Neurospora dictyophora WZ-497 - Xin Li; Yuan-Xiang Gong; Li Feng; Xin-Jia Wang; Jing-Wen Wang; An-Xin Zhang; Ning-Hua Tan; Zhe Wang (Phytochemistry, 2023)

Spatial patterns and interspecific relationships of two dominant cushion plants at three elevations on the Kunlun Mountain, China - Rui–ming Zhao; Hua Zhang; Li–zhe An (Environmental Science and Pollution Research, 2020)

Thylacospermum caespitosum population structure and cushion species community diversity along an altitudinal gradient - Rui–ming Zhao; Hua Zhang; Li–zhe An (Environmental Science and Pollution Research, 2018)

The occurrence and risk assessment of five organophosphorus pesticides in river water from Shangyu, China - Hao Chen; Jianqiang Zhu; Zhe Li; An Chen; Quan Zhang (Environmental Monitoring and Assessment, 2016)

Frost-free season lengthening and its potential cause in the Tibetan Plateau from 1960 to 2010 - Dan Zhang; Wenhui Xu; Jiayun Li; Zhe Cai; Di An (Theoretical and Applied Climatology, 2014)

E2F1-mediated DNA damage is implicated in 8-Cl-adenosine-induced chromosome missegregation and apoptosis in human lung cancer H1299 cells - Yu-Ying Han; Zhe Zhou; Ji-Xiang Cao; Ya-Qiong Jin; Shu-Yan Li; Ju-Hua Ni; Guo-Shun An; Yu-Xiang Zhang; Hong-Ti Jia (Molecular and Cellular Biochemistry, 2013)

Cloning, expression and characterization of trehalose-6-phosphate phosphatase from a psychrotrophic bacterium, Arthrobacter strain A3 - Yuan-ting Li; Hai-hong Zhang; Hong-mei Sheng; Li-zhe An (World Journal of Microbiology and Biotechnology, 2012)

Regulation of expression of trehalose-6-phosphate synthase during cold shock in Arthrobacter strain A3 - Xi-Ming Chen; Ying Jiang; Yuan-Ting Li; Hai-Hong Zhang; Jie Li; Xing Chen; Qi Zhao; Jing Zhao; Jing Si; Zhi-Wei Lin; Hua Zhang; Paul Dyson; et al. (Extremophiles, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

The catalytic efficiency of trehalose-6-phosphate synthase is effected by the N-loop at low temperatures - Ying Jiang; Xi-Ming Chen; Ya-Jie Liu; Yuan-Ting Li; Hai-Hong Zhang; Paul Dyson; Hong-Mei Sheng; Li-Zhe An (Archives of Microbiology, 2010)

Isolation and characterization of microsatellite loci in Peganum harmala (Peganaceae), an important resist-drought and medicinal plant - Jin Han; Li-Zhe An (Conservation Genetics, 2009)

CbCOR15, A Cold-Regulated Gene from Alpine Chorispora bungeana, Confers Cold Tolerance in Transgenic Tobacco - Jing Si; Jian-hui Wang; Li-jing Zhang; Hua Zhang; Ya-jie Liu; Li-zhe An (Journal of Plant Biology, 2009)

CbLEA, a NovelLEA Gene fromChorispora bungeana, Confers Cold Tolerance in Transgenic Tobacco - Hua Zhang; Rui Xia Zhou; Li Jing Zhang; Ruo Yu Wang; Li Zhe An (Journal of Plant Biology, 2007)

Variations of stomatal density and carbon isotope values of Picea crassifolia at different altitudes in the Qilian Mountains - Wei-ya Qiang; Xun-ling Wang; Tuo Chen; Hu-yuan Feng; Li-zhe An; Yuan-qin He; Gang Wang (Trees, 2003)